Implementasi Pemasaran Digitalisasi Jasa Fotografi Berbasis Web - Linda, Deppi; Nurlistiani, Rini; Nursiyanto, Nursiyanto; Zulkarnaini, Zulkarnaini; Purnomo, Hendri (Jurnal Informatika, 2024)
As the digital era develops, the need for photography services is increasing. To meet their needs, many individuals and organizations seek photography services for various purposes, such as personal photo shoots, weddings, and other photography packages. When booking a photography studio, we often encounter obstacles such as the difficulty of finding a suitable studio, determining the price and package, and the slow booking process. By digitalization web-based photography service booking market, we have found a solution that allows customers to easily search for photography studios, view portfolios, and compare prices and packages offered. This allows the photography studio to expand its market reach, faster reservations, and improve the quality of its services. They used PHP programming language and Extreme Programming (XP) method to create a web-based information system to design a photo booking marketplace. The system aims to simplify the process of online photo booking in the region